Tapping into family power: Enhancing English learning for Chinese children in Banda Aceh through parental involvement (Englisia : Journal of Language, Education, and Humanities, 2024)
Learning English at an early age is believed to lead to a significant improvement in children's language skills. Parental involvement is thought to have a positive influence on children's development in learning English as a second/foreign language. A preliminary study found that Chinese parents are actively involved in helping their children learn English. Therefore, this study aims to investigate the types of parental involvement of Chinese parents and their roles in helping their children learn English in Banda Aceh, Indonesia. The focus of this study is on six types of parental involvement (parenting, communicating, volunteering, supervising children's learning at home, decision making, and collaborating with the community) and five roles of parents (motivators, models, facilitators, sources of knowledge, and coordinators) in children's education as proposed by Epstein (2011). The participants of this study are ten Chinese parents, seven mothers and three fathers, who have enrolled their children for early English language learning in one of the private courses in Banda Aceh, Indonesia. This study used a qualitative approach and was conducted through interviews. The findings show that Chinese parents engage in four types of parental involvement: parenting, communication, monitoring children's learning at home, and decision making. They also fulfil five parental roles in their children's language learning: motivators, models, facilitators, knowledge sources and coordinators. As this study focuses on parental involvement in children's English learning at primary school level, it is suggested that further research should aim to examine parental involvement in children's English learning at different levels of education, such as middle school or senior high school.
Keywords: English language learning; Chinese children; Parental involvement; Roles of parents